Myofibrillar protein synthesis and muscle hypertrophy individualized responses to systematically changing resistance training variables in trained young men - Damas, Felipe; Angleri, Vitor; Phillips, Stuart M.; Witard, Oliver C.; Ugrinowitsch, Carlos; Santanielo, Natalia; Soligon, Samuel D.; Costa, Luiz A. R.; Lixandrão, Manoel E.; Conceição, Miguel S.; Libardi, Cleiton A. (Journal of applied physiology (1985), 2019)
The manipulation of resistance training (RT) variables is used among athletes, recreational exercisers, and compromised populations (e.g., elderly) attempting to potentiate muscle hypertrophy. However, it is unknown whether an individual’s inherent predisposition dictates the RT-induced muscle hypertrophic response. Resistance-trained young [26 (3) y] men ( n = 20) performed 8 wk unilateral RT (2 times/wk), with 1 leg randomly assigned to a standard progressive RT [control (CON)] and the contralateral leg to a variable RT (VAR; modulating exercise load, volume, contraction type, and interset rest interval). The VAR leg completed all 4 RT variations every 2 wk. Bilateral vastus lateralis cross-sectional area (CSA) was measured, pre- and post-RT and acute integrated myofibrillar protein synthesis (MyoPS) rates were assessed at rest and over 48 h following the final RT session. Muscle CSA increase was similar between CON and VAR ( P > 0.05), despite higher total training volume (TTV) in VAR ( P < 0.05). The 0–48-h integrated MyoPS increase postexercise was slightly greater for VAR than CON ( P < 0.05). All participants were considered “responders” to RT, although none benefited to a greater extent from a specific protocol. Between-subjects variability (MyoPS, 3.30%; CSA, 37.8%) was 40-fold greater than the intrasubject (between legs) variability (MyoPS, 0.08%; CSA, 0.9%). The higher TTV and greater MyoPS response in VAR did not translate to a greater muscle hypertrophic response. Manipulating common RT variables elicited similar muscle hypertrophy than a standard progressive RT program in trained young men. Intrinsic individual factors are key determinants of the MyoPS and change in muscle CSA compared with extrinsic manipulation of common RT variables. NEW & NOTEWORTHY Systematically manipulating resistance training (RT) variables during RT augments the stimulation of myofibrillar protein synthesis (MyoPS) and training volume but fails to potentiate muscle hypertrophy compared with a standard progressive RT. Any modest further MyoPS increase and higher training volumes do not reflect in a greater hypertrophic response. Between-subject variability was 40-fold greater than the variability promoted by extrinsic manipulation of RT variables, indicating that individual intrinsic factors are stronger determinants of the hypertrophic response.